The effect of SPOC hybrid model on deep learning effectiveness : A systematic literature review - Pan, Bo; Fatmawati, Latada; Shao, Yubo (North American Business Press, 2023)
The hybrid model of SPOC (Small Private Online Course) may have an impact on the effectiveness of deep learning. Nevertheless, few studies have validated the relationship between SPOC and deep learning effectiveness. This systematic review focuses on exploring the impact of the blended model of SPOC on deep learning effectiveness. The article delves into the three major SPOC categories in deep learning and the effects of deep learning in SPOC mode. In addition, the article explores various factors that influence the effectiveness of SPOC on deep learning. To accomplish this, an exhaustive review of the relevant literature was conducted to reveal potential connections and interactions between the SPOC blended model and deep learning effectiveness. This study provides educators and researchers with insights on how to more effectively combine SPOC and deep learning to optimize teaching and learning experiences.